2017
DOI: 10.1186/s12951-017-0292-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and properties of nano-LiCoO2 synthesized by pre-organized single source precursors: Li-ion diffusivity, electrochemistry and biological assessment

Abstract: BackgroundLiCoO2 is one of the most used cathode materials in Li-ion batteries. Its conventional synthesis requires high temperature (>800 °C) and long heating time (>24 h) to obtain the micronscale rhombohedral layered high-temperature phase of LiCoO2 (HT-LCO). Nanoscale HT-LCO is of interest to improve the battery performance as the lithium (Li+) ion pathway is expected to be shorter in nanoparticles as compared to micron sized ones. Since batteries typically get recycled, the exposure to nanoparticles durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“… nano‐LCO: According to our experimental measurements, the capacity is 25 % higher than that of HT‐LCO . The value for the energy density was calculated from this specific capacity by using a potential of 3.9 V, and the number of charging cycles was assumed to be similar to that of HT‐LCO; nano‐LMP: With regard to capacity, 90 % of the value achieved by making nanoparticles of LMP and ball milling reported by Kwon and co‐workers was assumed; the value for the energy density was calculated from this by applying a value for the potential of 4.1 V . For the number of charging cycles, the same value as for LFP was used as both of these materials have a similar olivine structure. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… nano‐LCO: According to our experimental measurements, the capacity is 25 % higher than that of HT‐LCO . The value for the energy density was calculated from this specific capacity by using a potential of 3.9 V, and the number of charging cycles was assumed to be similar to that of HT‐LCO; nano‐LMP: With regard to capacity, 90 % of the value achieved by making nanoparticles of LMP and ball milling reported by Kwon and co‐workers was assumed; the value for the energy density was calculated from this by applying a value for the potential of 4.1 V . For the number of charging cycles, the same value as for LFP was used as both of these materials have a similar olivine structure. …”
Section: Resultsmentioning
confidence: 99%
“…nano‐LCO: According to our experimental measurements, the capacity is 25 % higher than that of HT‐LCO . The value for the energy density was calculated from this specific capacity by using a potential of 3.9 V, and the number of charging cycles was assumed to be similar to that of HT‐LCO;…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, ultrafine LiCoO 2 powders have advantages over commercial LiCoO 2 powders. For example, the high initial charge/discharge capacities and rate capability has been confirmed . Xuanye et al.…”
Section: Ultrafine Licoo2mentioning
confidence: 88%
“…Therefore, ultrafine LiCoO 2 powders have advantages over commercial LiCoO 2 powders. For example, the high initial charge/discharge capaci-ties and rate capability has been confirmed [38][39][40][41][42][43]. Xuanye et al [44] showed that ultrafine-sized LiCoO 2 exhibits a high initial discharge specific capacity of 166.7 mAh g -1 at 0.2°C.…”
Section: Ultrafine Licoomentioning
confidence: 94%